A comparative study on the efficacy of whitening dentifrices, S.Y. 1996-1997 - Dino, Mariejecelle P.; Ng, Rebecca C.; Medina, Ma. Concepcion B. (Adviser).
The objective of the in vitro study undertaken was to compare the three whitening toothpastes and determine their effectiveness, with a regular toothpaste as control. Three whiitening toothpastes, Colgate Platinum, Rembrandt Whitening Toothpaste, Arm & Hammer Dental Care Whitening Toothpaste, and a regular toothpaste, Colgate with fluoride, were used for the experiment. A total of 20 freshly extracted teeth were used for the study ( 5 for each toothpaste brand). Tooth color was measured using the Bioform shade guide before and after the experiment. The extracted teeth were cleaned and divided into 4 groups. The teeth were then brushed 1960 strokes. The experiment showed that the groups using whitening toothpastes displayed significant whitening versus the group which used regular toothpaste. It can be concluded that the three specialty whitening toothpastes tested produce whitening performance that is over and above the regular toothpaste and that there is a difference between the whitening efficacy of one whitening toothpaste brand versus another whitening toothpaste brand. Maximum whitening effect can be achieved thru the use of proper brushing techniques and oral hygiene. It is therefore the responsibility of every dental professional to educate their patients. In vivo studies with the use of a colorimeter to measure color changes are recommended for future studies.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.